Kardiomiopati peripartum vs Kardiomiopati peripartum dengan preeklamsia: dari pendekatan biomolekuler hingga manajemen - Fahreza, Lufthi; Winato, Brigad Mahardika; Nugrahani, Annisa Dewi; Arianto, Steven (Fakultas Kedokteran Universitas Trisakti, 2024)
Peripartum cardiomyopathy (PPCM) is a potentially life-threatening pregnancy-related condition that typically occurs during the peripartum period. It is characterized by impaired function of the left ventricle and heart failure. Preeclampsia is recognized as a risk factor for PPCM and can coexist with this condition. However, there is limited available data that explains the variations in treatment approaches between cases of peripartum cardiomyopathy with and without preeclampsia. Hence, the objective of this study is to examine the distinctions between PPCM and PPCM accompanied by preeclampsia, encompassing their molecular, pathogenic, and pathophysiological aspects, as well as their treatment and management strategies. These factors could potentially play a role in influencing the treatment of patients diagnosed with peripartum cardiomyopathy. A thorough review of existing literature was conducted between June and August 2023. Articles were retrieved from medical databases including PubMed, EBSCOhost, Medline, SAGE, JSTOR, and ScienceDirect, utilizing keywords such as